UPAYA MENINGKATKAN KESADARAN REMAJA AKAN KESETARAAN GENDER BERDASARKAN MORAL KRISTIANI - Bramantyo, Rafael Dimas; Prodeita, Theresia Vita (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
Discrimination and subordination of women in society are still common. Women experience injustice in various fields of life due to the patriarchal culture adopted by society. The gender equality movement is needed to fight for equal relations between men and women. This study aims to analyze the gender equality movement in Asia, especially in Indonesia based on Christian morals. The author uses a library research method by examining the main book